In vitro characterization of baloxavir acid, a first-in-class cap-dependent endonuclease inhibitor of the influenza virus polymerase PA subunit - Noshi, Takeshi; Kitano, Mitsutaka; Taniguchi, Keiichi; Yamamoto, Atsuko; Omoto, Shinya; Baba, Keiko; Hashimoto, Takashi; Ishida, Kayo; Kushima, Yukihiro; Hattori, Kazunari; Kawai, Makoto; Yoshida, Ryu; et al. (Antiviral research, 2018)
Cap-dependent endonuclease (CEN) resides in the PA subunit of the influenza virus and mediates the critical “cap-snatching” step of viral RNA transcription, which is considered to be a promising anti-influenza target. Here, we describe in vitro characterization of a novel CEN inhibitor, baloxavir acid (BXA), the active form of baloxavir marboxil (BXM). BXA inhibits viral RNA transcription via selective inhibition of CEN activity in enzymatic assays, and inhibits viral replication in infected cells without cytotoxicity in cytopathic effect assays. The antiviral activity of BXA is also confirmed in yield reduction assays with seasonal type A and B viruses, including neuraminidase inhibitor-resistant strains. Furthermore, BXA shows broad potency against various subtypes of influenza A viruses (H1N2, H5N1, H5N2, H5N6, H7N9 and H9N2). Additionally, serial passages of the viruses in the presence of BXA result in isolation of PA/I38T variants with reduced BXA susceptibility. Phenotypic and genotypic analyses with reverse genetics demonstrate the mechanism of BXA action via CEN inhibition in infected cells. These results reveal the in vitro characteristics of BXA and support clinical use of BXM to treat influenza. •In vitro characterization of a CEN inhibitor baloxavir acid (BXA), the active form of baloxavir marboxil, was conducted.•BXA selectively blocks CEN activity of the viral polymerase complex in enzymatic assay.•BXA exhibits potent and broad activities against various types of influenza viruses.•In vitro drug resistant isolation study supports BXA targets CEN of PA subunit.